Una mirada desde la óptica de la de psicología jurídica en privados de la libertad, consumidores de spa, en el establecimiento penitenciario y carcelario de alta y mediana seguridad de Combita (2021)
This is an investigation carried out from the perspective of Legal Psychology to those deprived of liberty that make up the residential Therapeutic Community of the High and Medium Security Penitentiary Establishment of Combita (Boyacá) that aims to prevent or intervene the consumption of psychoactive substances in the context of the prison environment that bring legal effects to legal benefits established in Law 65 of 1993 - Penitentiary and Prison Code, implying mental health and resocialization of inmates. Four psychological tests were applied to those deprived of liberty in two moments, the first corresponding to a pre-test and the second as a post-test, in which it was intended to perform a quantitative analysis on the findings resulting from the applied psychological instruments.